Causes of Non-Marketable Fruit Production throughout the Strawberry Harvest Season in Subtropical Environments - Kirschbaum, Daniel Santiago (2014)
The objective of this study was to analyze the distribution pattern of the different causes of the production of non-marketable fruit throughout the harvest season for several strawberry cultivars grown in a sub-tropical climate: ‘Carmela’, ‘Elyana’, ‘Florida Festival’, ‘Radiance’, ‘Macarena’ and ‘Candonga’. Fruit was harvested 2-3 times a week between June and October. In June, the main cause of non-marketable fruit production was fruit rot (90%). In July and August, fruit was mostly discarded because of small size (40%), or it was malformed (40%). In September and October the primary cause of non-marketable fruit was small size (65-87%). ‘Elyana’ had least discarded fruit (9 fruits/plant), while ‘Florida Festival’ had the highest rate of non-marketable fruit (18 fruits/plant); however, this cultivar had a marketable yield 31% higher than ‘Elyana’. Knowing what causes the production of non-marketable fruit in different months allows the establishment of correlations between losses and weather factors, the genotype, the phonological stage, and the physiology of the plant. Such knowledge contributes to decision making for the implementation of crop management measures that mitigate fruit losses.